85 point plz answer

1. Combine the like terms to simplify the expression.
9x2 + 8y2 + 4y2 – 3x


a. 6x + 12y2


b. 9x2 + 12y4 – 3x


c. 6x + 12y4


d. 9x2 + 12y2 – 3x

2. Use the Distributive Property and simplify the expression.

4+2(3x−1)+9

a. 3x + 14


b. 6x + 15


c. 6x + 11


d. 5x + 14

Respuesta :

Answer:

Step-by-step explanation:

1. Combine the like terms

9x2 + 8y2 + 4y2 – 3x

= 9x2 + (8y2 + 4y2) – 3x

= 9x2 + 12y2 – 3x

The answer is d.

2. Use the Distributive Property

4+2(3x−1)+9

= 4+2*3x−2*1+9

= 4+6x-2+9

= 6x+4-2+9

= 6x + 11

The answer id c.

msm555

Answer:

1. Combine the like terms to simplify the expression.

9x2 + 8y2 + 4y2 – 3x

answer:d.9x²+12y²-3x

2. Use the Distributive Property and simplify the expression.

4+2(3x−1)+9

answer:

4+6x-2+9

=c.6x-11

ACCESS MORE